National Alliance of Stakeholders for the Wheat Sector in Lebanon: Multistakeholder Workshop Report - El Amil, Rola; Dhehibi, Boubaker; Machlab, Hassan; M. Oumer, Ali; Saad, Sarah; Akramov, Kamiljon; Baum, Michael (International Center for Agricultural Research in the Dry Areas, 2023)
On July 24, 2023, the International Center for Agricultural Research in the Dry Areas (ICARDA) and the Lebanese Agricultural Research Institute (LARI) under the Ministry of Agriculture organized a Multistakeholder Workshop on “National Alliance of Stakeholders for the Wheat Sector in Lebanon”. The agenda of the workshop is provided in Appendix 1. More than 20 representatives of various stakeholders attended the workshop, including officials of key government ministries and agencies, researchers from multiple research institutes, non-governmental and non-profit organizations, representatives of the United Nations (UN) agencies, and the private sector.